Impact on life Style Changes and Mental Health of Medical and Non-medical Students During Covid-19 Pandemic (Update Dental College Journal, 2024)
Background: Lifestyle is a part of the determinants of people's way of life. It is someone’s way of living; the thing that person or a particular group of people usually do. The relationships of lifestyle changes with a pandemic situation between medical & non-medical should be highly considered. Objectives: To find out the impact of the Covid-19 pandemic on lifestyle changes and mental health between medical and non-medical students. Methods: A cross-sectional study was carried out among 200 respondents in between 8 November 2020 to 9 December 2020, of which 100 students were from medical and 100 were from non-medical backgrounds. A self-administrative structured questionnaire was sent randomly to the medical and non-medical students by using online google form. The informed written consent was taken from the participants and the confidentiality of data were maintained properly. Results: Certain degree of precautionary measures is taken by students to combat Covid-19 pandemic situation, role & source of social media, injecting disinfectant directly into the blood, panic buying during covid-19 and problem facing while using online platform for education purpose had some association where (p